The Power of Platforms: A Critical Analysis of Postcolonial Dynamics and Cultural Hybridity in EFL Collaborative Digital Story Telling - Hantari, Winda; Ali Imron (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2024)
Rapid advancements in technology have had a profound impact on educational practices, particularly in language learning, where accessibility, interactivity, and collaboration have become central themes. This paper explores the integration of digital platforms such as Padlet, into English as a Foreign Language (EFL) classroom, with a particular focus on collaborative storytelling as a means of examining cultural hybridity, tradition, and modernity. Framed through a postcolonial lens, the study investigates how digital storytelling facilitates students’ negotiation of cultural values and postcolonial dynamics within a collaborative creative process. The findings suggest that digital storytelling platform provides EFL learners with valuable opportunities to critically engage with cultural identities and power dynamics, while simultaneously enhancing their creative writing skills. This study underscores the potential of technology-assisted learning to facilitate meaningful dialogue and critical reflection on cultural hybridity in contemporary educational context.